Potential of biomarkers during pharmacological therapy setting for postmenopausal osteoporosis: a systematic review - Filippo Migliorini; Nicola Maffulli; Filippo Spiezia; Giuseppe Maria Peretti; Markus Tingart; Riccardo Giorgino (Journal of Orthopaedic Surgery and Research, 2021)
Abstract Background Biochemical markers of bone turnover (BTMs), such as the bone alkaline phosphatase (bALP), procollagen type I N propeptide (PINP), serum cross-linked C-telopeptides of type I collagen (bCTx), and urinary cross-linked N-telopeptides of type I collagen (NTx), are used to manage therapy monitoring in osteoporotic patients. This systematic review analyzed the potential of these BMTs in predicting the clinical outcomes in terms of BMD, t-score, rate of fractures, and adverse events during the therapy setting in postmenopausal osteoporosis. Methods All randomized clinical trials (RCTs) reporting data on biomarkers for postmenopausal osteoporosis were accessed. Only articles reporting quantitative data on the level of biomarkers at baseline and on the outcomes of interest at the last follow-up were eligible. Results A total of 36,706 patients were retrieved. Greater values of bALP were associated with a greater rate of vertebral (P = 0.001) and non-vertebral fractures (P = 0.0001). Greater values of NTx at baseline were associated with a greater rate of adverse events at the last follow-up (P = 0.02). Greater values of CTx at baseline were associated with a greater rate of adverse events leading to discontinuation (P = 0.04), gastrointestinal adverse events (P = 0.0001), musculoskeletal adverse events (P = 0.04), and mortality (P = 0.04). Greater values of PINP at baseline were associated with greater rates of gastrointestinal adverse events (P = 0.02) at the last follow-up. Conclusion The present analysis supports the adoption of BMTs during pharmacological therapy setting of patients suffering from osteoporosis. Level of evidence I, systematic review of RCTs